Occurrence of 1,4-dioxane in domestic wastewater and processed water: A case study of Thailand’s central plain - Rattanit Mantiya; Kusanthia Ladawan; Sethbhakdi Pavin; Pornwongthong Peerapong (E3S Web of Conferences)
1,4-Dioxane is an emerging water contaminant and probable human carcinogen. Its use in various applications and improper waste management can lead to water contamination. This study surveyed 1,4-dioxane contamination in domestic wastewater and water from Thailand’s central plain. Samples of influent, effluent, and activated sludge from seven domestic wastewater treatment plants, as well as tap water from 28 public water systems, were collected and analyzed for 1,4-dioxane. The results showed 1,4-dioxane presence in all wastewater samples, with concentrations ranging from 4.34 to 1285.44 μg/L and effluent loads between 0.54 and 254.95 kg/day. Additionally, 1,4-dioxane was detected in five public water systems (17.86% of the sites) at concentrations between 44.54 and 81.24 μg/L. These findings indicate that some municipal water and wastewater treatment plants in Thailand’s central plain are not effectively removing 1,4-dioxane, highlighting the need for monitoring and improved treatment technologies to manage contamination in the area.